Diversity of plankton species in different ecosystems on Beras Basah Island, Bontang, East Kalimantan - Imam Fadila, Muhammad; Anjasmara, Aang Setyawan; Rizal, Daisy Rahma; Rusdi, Rismawaty; Reynalta, Ricko (Bioeksperimen: Jurnal Penelitian Biologi, 2026)
Beras Basah Island, located in the coastal waters of Bontang City, East Kalimantan, is a marine conservation area characterized by diverse coastal ecosystems, including marine waters, coral reefs, and seagrass beds. These ecosystems support various aquatic organisms, including plankton communities that play a key role in marine food webs. This study aimed to examine the composition, abundance, and diversity of plankton across three different ecosystems around Beras Basah Island. Sampling was conducted in May 2025 using a purposive sampling method at three stations representing marine waters, coral reefs, and seagrass bed. Plankton samples were collected using a 20 µm mesh plankton net and preserved with Lugol’s solution. The data were analyzed to determine plankton abundance, Shannon–Wiener diversity index (H’), and evenness index (E). A total of 13 plankton species were identified, consisting of 10 phytoplankton species (Bacillariophyceae and Dinophyceae) and 3 zooplankton species (Ciliata and Crustacea). The Shannon–Wiener diversity index ranged from 2.17 to 2.30, indicating moderate diversity, while evenness values ranged from 0.94 to 0.98, suggesting a relatively uniform distribution of individuals among species. Phytoplankton dominated the plankton community across all ecosystems, with the highest abundance recorded in the seagrass ecosystem (1,732 individuals L⁻¹). These findings indicate that plankton communities are relatively consistent across different coastal ecosystems in the waters of Beras Basah Island.